(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
The government aims for 90% of infants and toddlers to visit posyandu (community health posts), but this target is unmet. To improve knowledge among parents, a website called "PUISI LITA" was developed to provide information in the digital era. This study assessed the website’s effectiveness compared to the traditional KIA child health booklet using WebQual 4.0, which measures usability, information, and interaction quality. A true experiment with a pretest-posttest control group design was conducted. 43 parents in the experimental group used the PUISI LITA website, while the control group used the KIA booklet (n=43). The Mann-Whitney test showed significant differences (p<0.05) in all three quality dimensions: usability (experimental: 55.33, control: 31.67), information (experimental: 54.19, control: 32.81), and interaction (experimental: 57.22, control: 29.78). These results indicate that the PUISI LITA website is more effective than the KIA booklet in improving parents’ knowledge about infant and toddler care. In conclusion, the PUISI LITA website is a promising tool to increase parental knowledge and potentially improve posyandu visit rates.